New or Old Relations? Brazil’s Technical Assistance in Mozambique during the Lula da Silva Administration - Elga Lessa De Almedia (Íconos)
The arrival of Lula da Silva as President of the Republic in 2003 allowed Brazil to re-initiate relations with African countries, which had chilled during the period immediately following re-democratization. African countries are now the main recipients of technical assistance under the international solidarity discourse and for the compensation of historic debt with these countries. However, the increase in foreign aid seems to be related to another aspect as well: the intensification of economic relations in the southern axis. The connection between Brazil and Mozambique is a clear example that allows for an understanding of how aid has been used as a tool by Brazilian foreign policy. This has resulted in increased commercial exchange, in the reinforcement of Brazil’s presence on the continent, and especially, in Brazilian companies’ participation in “megaprojects.” It is therefore interesting to understand the nuances of this presence, considering the interests involved.